Durability of carbon fibre reinforced polymer laminates used to reinforced concrete structures - Cabral-Fonseca, S. (2011)
This work is part of a much larger research study that is being made to predict the long-term behaviour of several commercial CFRP laminate/adhesive systems used in the rehabilitation of concrete structures. In the whole project it is recognized that the durability of these solutions depends, not only on the durability of the composite materials but also on the performance of the systems used to bond them to the concrete. The present document provides details about the part of the investigation concerning the durability of CFRP laminates.